Les logiques sociales de l’iconographie contestataire : le cas du quartier d’El Príncipe à Ceuta - Alicia Fernández García (Amnis)
Searching a nationalist propaganda, Ceuta’s public authorities, a Spanish enclave in Morocco, have carried out an instrumentalisation of urban iconography and place names. Contrary to the public art of town center’s official monuments, in El Principe’s peripheral district, urban art is born in a context of social downgrading. It appears as a spontaneous practice going beyond the desire to beautify while trying to subvert the social model. In the manner of Mexican muralists who claimed a social and ideological function to creation, Ceuta’s public space, and notably its public walls, serve a community social expression whose purposes are multiple. In the case of El Principe, the drug mafias have tried to mark this territory with their social footprint and to dispute its monopoly with local authorities. But the streets of this district have also become the expression of social malaise and religious radicalism. This contribution is thus a study on El Principe’s walls as spaces of jihadist propaganda, as places of a mafia counter-culture and protest iconography.